(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: The Novel Coronavirus shock affected impacted the entire world. It affected the hospitality sector badly during the pandemic situation. The hotel industry adopted various strategies to overcome this pandemic situation. Objectives: The study attempts to find out the conditions and the re-building strategies adopted by the hospitality industry such as the amenities and facilities provided to the guest and also the safety measures taken by the hotels during the pandemic situation. Methodology: The study is descriptive in nature. During the pandemic situation there were several problems faced by the hotel industry. The various problems were discussed with the operating departmental heads and the other hotel staff such as executives, associates and job trainees. The primary data was collected from the hotel staff through questionnaire method using the online platforms like Google forms and it was send to the respective persons. 250 samples were taken for the study which included core departmental heads, employees and the trainees of the hotels. Stratified random sampling techniques were used for collecting the data. The data collected was classified and tabulated. The data was analyzed by using different statistical techniques like percentage analysis, Correlation analysis with the help of IBM SPSS Version 23. Results: Safety measures taken by the departments included restaurants being sanitized; rearranging the furniture for maintaining a social distancing; the kitchen staffs getting properly sanitized; wearing mask and gloves. Sterilizing and sanitizing the guest and their belongings before rooming the guest. The billing system was shifted more towards the electronic mode. The staff guided the guests to follow the instructions during their stay in the hotel. Conclusion: The hotel premises including the public areas and the lobby were sterilized and sanitized every two hours in most hotels. The workers were asked to work in staggered shifts. The guest who come to visit and stay in the hotel were made to feel safe and comfortable with the services.